Implementation of Cognitive Technologies in the Process of Joint Project Activities: Methodological Aspect - Kwiliński, Aleksy; Polcyn, Jan; Pająk, Krzysztof; Stępień, Sebastian (<center>Conference Proceedings Determinants Of Regional Development</center>; No 2 (2021): Conference Proceedings - VIII International Scientific Conference Determinants of Regional DevelopmentDO - 10.14595/CP/02/006, 2021)
The article defines the technical and logical-structural conditions for ensuring joint project activity on the basis of cognitive technologies. An algorithm was developed to support the approval of the decision on the outsourcing of project works on the terms of system outsourcing. A fuzzy logic algorithm for selecting a contractor for specific works within a specific project and providing support for the execution processes is proposed. The experimental part of the cognitive model is investigated on the basis of additive convolution of evaluation indicators. The pattern of calculation of relative degrees of advantage of indicators for estimation of potential outsourcers is created.